THE IMPACT OF OMNICHANNEL INTEGRATED MARKETING COMMUNICATIONS (IMC) ON RETAIL PRODUCT AND SERVICE SATISFACTION IN INDONESIA: AN ANALYSIS WITH AN OPEN ACCESS APPROACH - Zaenal Aripin; Didin Saepudin; Asep Gunawan (Organisasi Kreatif Indonesia Emas, 2024)
Integrated Marketing Communication (IMC) Omnichannel has become a key strategy for retail companies in Indonesia. This research aims to analyze the impact of IMC Omnichannel implementation on the satisfaction of retail products and services in Indonesia using an open access approach. The rapid development of technology and high internet penetration in Indonesia has prompted retail companies to shift to digital technology-based marketing. The objective of this study is to understand how the integration of various communication channels in IMC Omnichannel affects consumers' perceptions and levels of satisfaction with retail products and services in Indonesia. The research method used is descriptive qualitative, with primary data sources derived from relevant journals, books, and articles. Analysis was conducted by collecting and evaluating relevant information about IMC Omnichannel implementation and its impact on consumer satisfaction in the retail context in Indonesia. The research findings indicate that IMC Omnichannel implementation has a significant impact on the satisfaction of retail products and services in Indonesia. The integration of various communication channels allows companies to provide a more comprehensive and consistent shopping experience for consumers. Additionally, service quality, responsiveness to consumer needs, and personalized shopping experiences also play a crucial role in influencing consumer satisfaction in the context of IMC Omnichannel.